The conquest involving Viking war-bands in the process of the Piast State formation. A critique - Kara, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2014)
A concept repudiating endogenous origins of the Piast state has presently enjoyed considerable popularity in Polish historiography and archaeology. The scholars who support this hypothesis propound that the Piast state was formed in an act of conquest by a foreign military elite. Ideas akin to this supposition, based on the so called social conflict theory, were for the first time formulated in social and historical sciences in the second half of the nineteenth and in the early twentieth century. This paper seeks to examine this thesis and collate it with the postulate that the social contract (finalised with a ritual pact) was the fundamental cause of the origin of the primary Piast domain.